1984
DOI: 10.1104/pp.74.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity on Nodule Formation by Soybean

Abstract: A split-root growth system was employed to evaluate the effect of NaCl on nodule formation by soybean (Glycine max L. Meff. cv Davis). By applying the salinity stress and rhizobial inoculum to only one-half the root system, the effects of salinity on shoot growth were eliminted in the nodulation process. Rhizobium colonization of inoculated root surfaces was not affected by the salt treatments (0.0, 26.6, 53.2, and 79.9 millimolar NaCI). While shoot dry weight remained unaffected by the treatments, total shoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
108
1
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(123 citation statements)
references
References 12 publications
8
108
1
6
Order By: Relevance
“…It has been estimated that 20% of the irrigated land in the world is presently affected by salinity (Yamaguchi and Blumwald 2005). Salt stress is reported to inhibit soybean germination and plant growth (Abel andMacKenzie 1964, Wang andShannon 1999), nodule formation (Singleton and Bohlool 1984), and seed yield (Parker et al 1983). Chloride is a major toxic element in soybean salt stress (Abel andMacKenzie 1964, Parker et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that 20% of the irrigated land in the world is presently affected by salinity (Yamaguchi and Blumwald 2005). Salt stress is reported to inhibit soybean germination and plant growth (Abel andMacKenzie 1964, Wang andShannon 1999), nodule formation (Singleton and Bohlool 1984), and seed yield (Parker et al 1983). Chloride is a major toxic element in soybean salt stress (Abel andMacKenzie 1964, Parker et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Saline conditions hamper germination, growth (Abel and Mackenzie, 1964;Wang and Shannon, 1999), and nodule formation (Singleton and Bohlool, 1984) in soybean, resulting in significant reductions in seed yield (Parker et al, 1983;Yang and Blanchar, 1993). Studies comparing genetically diverse cultivars have found significant differences in salt tolerance (Parker et al, 1983;Yang and Blanchar, 1993;Lee et al, 2008;Tuncturk et al, 2008;Ghassemi-Golezani et al, 2009;Hakeem et al, 2012;Karim et al, 2012;Mannan et al, 2012).…”
mentioning
confidence: 99%
“…토양생태계의 염류화 현상은 건조 지역에서 빈번하게 발생 하며, 지구온난화에 의해 수분 증발량이 증가되어 전세계 지 표면의 10%가 이미 염류화가 진행되었다 [1]. 염분이 토양에 존재할 경우 대부분 식물의 생장을 저해하고 염에 민감한 식 물인 콩과 식물의 경우는 고농도의 Cl -에 의해 잎의 황백화 와 광합성 저해로 생장이 억제된다 [2].…”
Section: Introductionunclassified